Perforin and Fas act together in the induction of apoptosis, and both are critical in the clearance of lymphocytic choriomeningitis virus infection - Rode, Miriam; Balkow, Sandra; Sobek, Vera; Brehm, Reina; Martin, Praxedis; Kersten, Astrid; Dumrese, Tilman; Stehle, Thomas; Müllbacher, Arno; Wallich, Reinhard; Simon, Markus M. (Journal of virology, 2004)
In this report we questioned the current view that the two principal cytotoxic pathways, the exocytosis and the Fas ligand (FasL)/Fas-mediated pathway, have largely nonoverlapping biological roles. For this purpose we have analyzed the response of mice that lack Fas as well as granzyme A (gzmA) and gzmB (FasxgzmAxB(-/-)) to infection with lymphocytic choriomeningitis virus (LCMV). We show that FasxgzmAxB(-/-) mice, in contrast to B6, Fas(-/-), and gzmAxB(-/-) mice, do not recover from a primary infection with LCMV, in spite of the expression of comparable numbers of LCMV-immune and gamma interferon-producing cytotoxic T lymphocytes (CTL) in all mouse strains tested. Ex vivo-derived FasxgzmAxB(-/-) CTL lacked nucleolytic activity and expressed reduced cytolytic activity compared to B6 and Fas(-/-) CTL. Furthermore, virus-immune CTL with functional FasL and perforin (gzmAxB(-/-)) are more potent in causing target cell apoptosis in vitro than those expressing FasL alone (perfxgzmAxB(-/-)). This synergistic effect of perforin on Fas-mediated nucleolysis of target cells is indicated by the fact that, compared to perfxgzmAxB(-/-) CTL, gzmAxB(-/-) CTL induced (i) an accelerated decrease in mitochondrial transmembrane potential, (ii) increased generation of reactive oxygen species, and (iii) accelerated phosphatidylserine exposure on plasma membranes. We conclude that perforin does not mediate recovery from LCMV by itself but plays a vital role in both gzmA/B and FasL/Fas-mediated CTL activities, including apoptosis and control of viral infections.